A Review: The Soluble Sugars Involved in The Process of Heartwood Formation - Arisandi, Rizki (Masyarakat Peneliti Kayu Indonesia, 2024)
This study aims to examine the soluble sugars involved in the process of heartwood formation using 87 journal articles and non-articles. The data used was collected through an online search with 5 keywords, namely “heartwood formation”, “reserve material of heartwood”, “non-structural carbohydrate of heartwood”, “starch of heartwood” and “sucrose of heartwood”. By removing irrelevant papers, 44 suitable journal articles and non-articles were found. Studies showed that monosaccharide fraction was the largest group compared to the other fractions as well as dominated by the hexose group. In addition, several species such as Swietenia mahagoni, Pinus sylvestris, Betula pendula, and Fagus sylvatica were detected more complete than other species in the fraction of soluble sugars (monosaccharides, disaccharides, trisaccharides, tetrasaccharides, alditol, and cyclitol). Based on previous studies, the contents of glucose and sucrose compounds were the major compound and plays an important role in storing energy reserves and the process of heartwood formation. Meanwhile, the levels of arabinose and galactose were the minor components in several species. Within tree variation, soluble sugars drop from the sapwood to the heartwood and from the top to the bottom of the tree. Subsequently, the alditols and cyclitols fractions need special issues, especially for tropical species related to their role.